Identifying evidence of the effectiveness of photovoice: a systematic review and meta-analysis of the international healthcare literature. (5th April 2021) - Halvorsrud, Kristoffer; Eylem, Ozlem; Mooney, Roisin; Haarmans, Maria; Bhui, Kamaldeep
Abstract: Background: Photovoice (PV) was conceptualized in the early 1990s to engage community members in capturing/communicating their lived experience narratives through photography. However, no meta-analyses in health research have assessed whether PV achieves its purported effects. Methods: We carried forward any relevant references from a previous review identifying PV studies before 2008 and searched MEDLINE, Embase, PsycINFO and Cochrane Central Register of Controlled Trials from 2008 up until October 2019. We included both published and grey literature, in any population or context. We assessed quality with the Effective Public Health Practice Project's (EPHPP) tool and pooled studies using the standardized mean difference (SMD) and 95% confidence intervals (CIs). Results: Twenty-eight studies were included, showing significant post-treatment effects only for health knowledge (SMD, 95% CIs = 0.41, 0.09 to 0.73, n = 16) and community functions (SMD, 95% CIs = 0.22, 0.03 to 0.40, n = 4). Strong heterogeneity was indicated for health knowledge, potentially explained by a larger effect in ethnic minority populations. There was insufficient follow-up data for health knowledge, while in follow-up for community functions the post-treatment effect was lost. Conclusions: PV's post-treatment effect on health knowledge did not translate into positive health behaviours or physical and mental health outcomes, longer-term community functions, or health service outcomes.